Challenges Faced by Halal Meat Industry: A Review - SHAHIDAN, NORSHAZILA; Amid, Azura (Halalsphere, 2023)
The demand trend for Halal meat and meat-based products among Muslims worldwide has increased in recent years. Meanwhile, the awareness among non-Muslims of Halal meat and meat products is due to their high quality and safety, thus resulting in more access to Halal meat and meat-based products for them. Due to the technological advancements in the meat processing sector, adulteration and fraud have grown more widespread due to the financial gain that can be realized. The issues associated with Halal meat have created an opportunity for researchers, scientists, consumers, manufacturers, and regulators to work together to determine whether meats produced in the industry are Halal, safe to be consumed and free from food-borne pathogens. Halal authentication technology can assist in addressing this issue, whilst as a result, can assist juries in assessing the status of the products with a high degree of precision. The objectives of this review paper are to discuss and review the challenges of the Halal meat industry, including the analytical procedures used to ensure that Halal meat products have long-term viability in Malaysia. The methods used to review the selected topics are searching the extant literature available in the online and offline sources, screening for topic inclusion, assessing, extracting and discussing the available data obtained in the updated journals. In conclusion, numerous challenges are faced by the Halal meat industry, and they should be addressed by focusing on realistic prospects to enhance the production of local meat, which is critical in guaranteeing the supply of Halalan Toyyiban meat is bounteous and secured.